DEVELOPMENT OF A CONCRETE-PICTORIAL-ABSTRACT (CPA) TEACHING MODULE TO IMPROVE NUMERATION LITERACY FOR ELEMENTARY SCHOOL STUDENTS - Faza Shafira; Andhin Dyas Fitriani; Mela Darmayanti (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2023)
This study aims to describe the design of the hypothesis and the feasibility of the Concrete-Pictorial-Abstract (CPA)-based multiplication teaching module to improve the numeracy literacy of elementary school students. The research method used is Design and Development (DD). This research procedure is Planning, Production, and Evaluation (PPE). This research result is a Concrete-Pictorial-Abstract (CPA) based teaching module on multiplication material in grade II Elementary School. The teaching modules have been validated by three experts: material experts, design experts, and linguists. The validation results from material experts get a percentage of 95%, design experts get a percentage of 89%, and linguists get a percentage of 92.5%. All validation results are included in the excellent criteria. The product was tested on students through a literacy ability test which was carried out through a pretest and post-test. The average result of the students' pretest scores is 50, and the average post-test results are 83. Thus, this teaching module is feasible and can improve students' numeracy literacy.